Dinamika N-Mineral Tanah Vertisols pada Berbagai Kombinasi Kualitas Seresah serta Serapan N Jagung Manis - Fitria Roviqowati; Purwanto Purwanto; Sri Hartati (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
TITLE : VERTISOLS N-MINERAL DYNAMICS IN SEVERAL LITTER QUALITY COMBINATION AND N-SWEET MAIZE UPTAKE. Problems are often found on farms in humid tropics that lack of balancing between number and availability of nutrients. The imbalance will lead to nutrients leaching, especially NO3- to the bottom layer. NO3- is the result of oxidation of NH4+ through a process called nitrification, hence it is important to control over the process as it. The purpose of this study was to determine the effect of litter quality Trimmings (based on the content of polyphenols and lignin) to the dynamics of N-NH4+ and N-NO3- land. This study is a field experimental with basic use Completely Group Randomized Design. The first factor is addition of Chromolaena odorata litter which represent high quality (lignin content 4.27 %, 17.12 % polyphenols), Tectona grandis litter representing low quality (lignin content of 14.54, 11.92 % polyphenols), and litter mixtures (Chromolaena odorata+Tectona grandis). The second factor dose of 5 Mg/ha, 12.5 Mg/ha, 20 Mg/ha. Analysis of the data using the F test, if the results of analysis of variance is significant, it forward to Duncan Test at α level = 0.05. The results showed that the addition of various quality litter significantly ( P